Investigation on high-temperature mechanical properties of Al–7Si–0.6Mg alloy by wire + arc additive manufacturing. Issue 14 (21st September 2020) - Li, Chengde; Gu, Huimin; Wang, Wei; Wang, Shuai; Ren, Lingling; Ming, Zhu; Zhai, Yuchun; Wang, Zhenbiao
Abstract : The room temperature and high temperature tensile properties of Al–7Si–0.6Mg alloy prepared by wire arc additive manufacturing have been investigated. The results show that the strengthening phase gradually coarsens and the eutectic silicon phase does not grow and agglomerate, meanwhile, the tensile strength and yield strength of the alloy gradually decrease with the increase of temperature. The high-temperature properties of the alloy are better than that of cast alloy. With the increase of temperature, the fracture of the alloy changes from ductile transgranular fracture to intergranular fracture.